Has China's Growth Gone from Miracle to Malady? - Eswar Prasad (Institute of Labor Economics (IZA), 2023)
China's remarkable run of persistently high growth in recent decades is all the more stunning in light of the country's low levels of financial and institutional development, state-dominated economy, and nondemocratic government. Notwithstanding the inefficient and risky growth model, the government has maneuvered the economy around various stresses without any major financial or economic crash. With a shrinking labor force and declining efficiency of investment, raising productivity growth is key to maintaining reasonable GDP growth. Unbalanced reforms, a schizophrenic approach to the role of the market versus the state, and strains in financial and property markets could result in significant volatility but a financial or economic collapse is not in the cards.
Keywords: F2; F3; F4; 330; growth rebalancing; sectoral reallocation; demographics; productivity growth; financial risks